2012
DOI: 10.1007/s10815-012-9851-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of human sperm with serine protease during density gradient centrifugation

Abstract: Purpose Seminal pathogens can bind specifically or nonspecifically to spermatozoa, rendering semen decontamination procedures ineffective, whereby vertical or horizontal transmission of the infection could occur. Serine proteases have been demonstrated to effectively inactivate viruses and to break pathogen-sperm bonds. However, the addition of a protease to density gradient layers during semen processing could negatively impact on sperm parameters. This study investigated the effect of the addition of a recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This method has proven effective in leaving the most robust sperm cells intact but also tends to solubilize sperm-membrane structures. Another broadly accepted method used to purify sperm cells away from other contaminants is by gradient centrifugation using Percoll or clinical-grade reagents like PureSperm, an isotonic salt solution containing silane-coated silica particles [Fourie et al 2012; Johnson et al 2011; Nicolas, et al 2012; Ostermeier, et al 2002]. In this case, a density gradient is used to separate the sperm cells from the larger and less dense somatic cells during centrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…This method has proven effective in leaving the most robust sperm cells intact but also tends to solubilize sperm-membrane structures. Another broadly accepted method used to purify sperm cells away from other contaminants is by gradient centrifugation using Percoll or clinical-grade reagents like PureSperm, an isotonic salt solution containing silane-coated silica particles [Fourie et al 2012; Johnson et al 2011; Nicolas, et al 2012; Ostermeier, et al 2002]. In this case, a density gradient is used to separate the sperm cells from the larger and less dense somatic cells during centrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of trypsin washing for decontamination of in vitro-produced bovine embryos is controversial. 16 In support of this contention, while several studies demonstrated that trypsin treatment is very effective for the removal or inactivation of BoHV-1, 7,10,17 other investigators found that the inclusion of trypsin solution in the washing procedure may be sufficient to strip BoHV-1 from the surface of the embryo but has no such effect on virus particles once inside. 14,18,19 Bielanski and Lalonde demonstrated that embryo cryopreservation may be regarded as a safety measure to decrease the potential risk or even mitigate disease transmission by embryo transfer.…”
Section: Methods For Virus Removal From Embryosmentioning
confidence: 96%